PERHITUNGAN PAJAK PENGHASILAN (PPh) BADAN PADA PKP RI KABUPATEN BOYOLALI TAHUN 2012 - Febriyanti Dewi Nugraheni; Adilistiono - Adilistiono (Politeknik Negeri Semarang, 2014)
The research with the title: THE CALCULATION INCOME TAX IN 2012 AT PKP RI OF BOYOLALI” have purpose to know the way of calculating of income tax, how to process of payment and report income Tax and also to comare the calculation of income Tax at PKP RI of Boyolali with Tax regulation, which PKP RI of Boyolali is effort organization as a tax subject. According to the result of the calculation, there are some differences between calculation PKP RI of Boyolali and calculation accourding to UU PPh No 36 of 2008. Accourding to the cooperation calculation, the tax payable is Rp 8.736.875,00 And accourding to the UU No 36 of 2008, the tax payable is Rp 11.228.125,00 this differences caused by fiscal.